Kajian Sosiolinguistik : Bahasa Feminisme pada Film “Barbie and The Three Musketeers” - Alya Hafizha; Annisa Putri Ramadhani; Marsha Nur Amalia (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study examines the use of feminist language in the film Barbie and the Three Musketeers (2009) from a sociolinguistic perspective. The film raises the theme of women's empowerment through the main character, Corinne, who struggles to prove that women can also be knights. In this context, the film utilizes dialogue and narrative to challenge gender stereotypes and depict solidarity between women in achieving common goals. This study uses a qualitative descriptive method with a note-taking technique in collecting data from conversations in the film. The results of the analysis show that the language used in the film reflects feminist values, including gender equality, courage, and cooperation between women. In addition, the film also successfully breaks down social barriers that hinder women and inspires viewers, especially the younger generation, to fight against norms that limit their potential. This study suggests the need to develop media content that supports women's empowerment to form a more inclusive and equal perception in society.